Recurrence risk factors in stage IA grade 1 endometrial cancer - Nwachukwu, Chika (J Gynecol Oncol, 2021)
OBJECTIVES: Patients with early-stage endometrial cancers (EC) with disease recurrences have worse survival outcomes. The purpose of this study was to identify clinical and pathologic factors that predict for all recurrences in stage IA grade 1 (IAG1) EC. METHODS: Records from patients diagnosed with EC were retrospectively reviewed. Baseline characteristics of 222 patients with IAG1 EC who underwent surgical resection were analyzed. Cox proportional hazard analysis was used to identify univariate and multivariate risk factors that predict for recurrence. RESULTS: Seventeen (7.65%) patients had recurrences. The 3-year cumulative incidence of recurrence were significantly higher for patients with time from biopsy to surgery ≥6 months (54% vs. 8%, p=0.003), simple hysterectomy with ovarian preservation vs. total hysterectomy and bilateral salpingo-oophorectomy (31% vs. 9%, p=0.032), any myometrial invasion vs. no invasion (18% vs. 2%, p=0.004), and tumor size ≥2 cm (15% vs. 2%, p=0.021). On, multivariate analysis, any myometrial invasion, increasing time from biopsy to surgery, and larger tumor size were independent predictors of any recurrence. Patients with recurrences had worse outcomes than those without (5-year overall survival [OS]=60%; 95% confidence interval [CI]=16%–86% vs. 5-year OS=95%; 95% CI=87%–99%, respectively, p=0.003). CONCLUSION: Time from biopsy to surgery, larger tumors, and myometrial invasion are the most important predictors of recurrence. Though the recurrence rates are generally low in IAG1 EC, the survival rate for the patients with recurrences was worse than those without. Identification of additional recurrence risk factors can help select patients who may benefit from adjuvant treatment.